COMPETENCY-BASED STANDARDS OF EDUCATION: PROBLEMS OF IMPLEMENTATION - Ekaterina M. Kuznetsova (Moscow Polytechnic University, 2016)
The article is aimed at analyzing the new federal standard of higher education in comparison with the preceding federal standard of the 3rd generation. The article includes a detailed analysis of the problems related to the nature of the standard and to the wording of competencies. These problems give rise to a large variety of interpretations of competencies in curricular programmes and other documents. The analysis showed that new standard of higher education presents no clear definition of competency and the suggested lists of competencies are formed without any argumentation. The new standard does not consider the conclusions of the international project TUNING Russia aimed at implementation of competency-based approach in national systems of higher education. As a possible solution to the defined problems the author suggests to invite employers, alumni and university staff to examine standards of higher education. But today the problems defined by the analysis that are identical to the problems of the preceding standard do not allow to consider the new standard of higher education to be an efficient instrument of implementation of the competency-based approach.